ICT AND THE NEW TEACHING AND LEARNING SPACES: FROM NEW PEDAGOGICAL MODELS TO VIRTUAL TEACHING AND LEARNING ENVIRONMENTS - Urakova Shoira, Urakova Shoira (Журнал иностранных языков и лингвистики, 2021)
The XXI st century confronts its citizenship with new choices, opportunities and challenges due to the ubiquitous presence of technology into all spheres of life: business and administration, government, education… The profound shifts undergone in the academic field must be viewed by thoughts on the new possibilities that new technologies involve.